2020
DOI: 10.1101/2020.11.26.400655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CA2 inhibition reduces the precision of hippocampal assembly reactivation

Abstract: The structured reactivation of hippocampal neuronal ensembles during fast synchronous oscillatory events termed sharp-wave ripples (SWRs) has been suggested to play a crucial role in the storage and use of memory. Activity in both the CA2 and CA3 subregions can proceed this population activity in CA1 and chronic inhibition of either region alters SWR oscillations. However, the precise contribution of CA2 to the oscillation, as well as to the reactivation of CA1 neurons within it, remains unclear. Here we emplo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…CA2 neurons may directly activate CA1 interneurons while triggering SWRs in the CA3 region, producing a multisynaptic delay of excitation 50 . Consistent with the possible inhibitory role of CA2 pyramidal cells, their chemogenetic silencing facilitates reactivation of CA1 cell assemblies while it reduces the temporal precision of the reactivation, often advancing the reactivation times 51 .…”
Section: Discussionmentioning
confidence: 78%
“…CA2 neurons may directly activate CA1 interneurons while triggering SWRs in the CA3 region, producing a multisynaptic delay of excitation 50 . Consistent with the possible inhibitory role of CA2 pyramidal cells, their chemogenetic silencing facilitates reactivation of CA1 cell assemblies while it reduces the temporal precision of the reactivation, often advancing the reactivation times 51 .…”
Section: Discussionmentioning
confidence: 78%
“…Importantly, this work does not refute that of prior studies which showed a lack of current goal representation in ripples (Carey et al, 2019;Gillespie et al, 2021), but rather argues for a more nuanced view of hippocampal ripples as a flexible mechanism that may be capable of altering their information content based on the cognitive demands of the current task. The transition from unstructured ripples to spatially organized replay across the first few trials argues that experience-dependent synaptic plasticity, perhaps across the CA3 or CA2 networks (He et al, 2021), is necessary to coordinate replay, even in a familiar environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although relatively small, the CA2 subfield is of particular interest as it forms the nexus of a powerfully excitatory disynaptic circuit that directly links cortical input to hippocampal output (Chevaleyre & Siegelbaum, 2010; Srinivas et al, 2017). Furthermore, accumulating evidence suggests that CA2 may have a unique role regulating hippocampal network excitability and organizing population activity (Boehringer et al, 2017; He et al, 2021; Lehr et al, 2021; Oliva, Fernández-Ruiz, Buzsáki, & Berényi, 2016; Oliva, Fernández-Ruiz, Leroy, & Siegelbaum, 2020). Recordings from surgically-resected hippocampal tissue from patients with refractory TLE revealed spontaneous interictal-like spikes in CA2, but the study could not address whether CA2 activity contributes to spontaneous recurring seizures (Wittner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%